Spatially constrained disulfide bond shuffling delays insulin aggregation and enhances neurotoxicity - Weida Qin; Ruomeng Li; Juan Liu; Jun Liu; Xiaoli Wang; Binbin Hu; Zhen Zheng; Zhilin Yu; Gongyu Li (Nature Communications)
Abstract Disulfide bond shuffling (DBS) critically influences protein aggregation and stability, yet its spatial constraints and biological implications remain poorly understood. Here, we demonstrate that insulin undergoes DBS within an extended spatial range up to ~19 Å, generating heterogeneous crosslinked oligomers that alter aggregation pathway. While DBS products initially delay aggregation by inhibiting primary nucleation and elongation steps, they ultimately promote the formation of distinct fibrillar structures with enhanced β-sheet content. Native ion mobility-mass spectrometry reveals molecular crosstalk between DBS products and native insulin via both covalent and non-covalent interactions. Notably, DBS-modified insulin fibrils exhibit significantly increased neurotoxicity in neuronal and pancreatic cells through mitochondrial apoptosis activation as supported by proteomic and biophysical analysis. Our findings underscore the importance of controlling DBS in insulin for therapeutic applications and provide insights into the role of disulfide dynamics in protein aggregation and cytotoxicity, with implications for insulin and broader protein misfolding contexts.